2018
DOI: 10.1002/cncr.31688
|View full text |Cite
|
Sign up to set email alerts
|

Oncologist volume and outcomes in older adults diagnosed with diffuse large B cell lymphoma

Abstract: In older adults diagnosed with DLBCL, receiving care from a provider with more experience treating lymphoma patients was associated with receipt of guideline-adherent therapy, reduced hospitalizations, and improved survival. Clinical volume may be an important factor in providing high-quality cancer care in the modern era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…37 More recently, our group found that Medicare beneficiaries with newly diagnosed DLBCL were more likely to receive standard immunochemotherapy and have better survival when managed by oncologists with greater experience treating older adults with lymphoma. 40 By focusing on outcomes after rituximab initiation, our current analysis suggests that provider experience may be associated with treatmentspecific management in addition to the therapy selection observed in our earlier work. 40 Along with establishing an association between physician volume and rituximab discontinuation, we found that early discontinuation was associated with worse survival.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…37 More recently, our group found that Medicare beneficiaries with newly diagnosed DLBCL were more likely to receive standard immunochemotherapy and have better survival when managed by oncologists with greater experience treating older adults with lymphoma. 40 By focusing on outcomes after rituximab initiation, our current analysis suggests that provider experience may be associated with treatmentspecific management in addition to the therapy selection observed in our earlier work. 40 Along with establishing an association between physician volume and rituximab discontinuation, we found that early discontinuation was associated with worse survival.…”
Section: Discussionmentioning
confidence: 75%
“…40 By focusing on outcomes after rituximab initiation, our current analysis suggests that provider experience may be associated with treatmentspecific management in addition to the therapy selection observed in our earlier work. 40 Along with establishing an association between physician volume and rituximab discontinuation, we found that early discontinuation was associated with worse survival. This is not surprising, given that multiple placebo-controlled clinical trials have established that rituximab-containing regimens improve survival in older adults with NHL.…”
Section: Discussionmentioning
confidence: 75%
“…As a facility‐level predictor of interest, we categorized whether patients were receiving care in a physician's office setting or a hospital outpatient setting. This was identified on the basis of the presence/absence of outpatient hospital‐based claims from each patient's provider on his or her index date of treatment …”
Section: Methodsmentioning
confidence: 99%
“…This was identified on the basis of the presence/absence of outpatient hospital-based claims from each patient's provider on his or her index date of treatment. 32…”
Section: Key Explanatory Variablesmentioning
confidence: 99%
“…Increased clinical volume has been associated with higher quality of care and better outcomes in hematologic cancers. [10][11][12][13][14] However, whether medical oncologists' clinical experience and volume affect patterns of care and outcomes of systemic therapy in solid cancers is unknown. In a review of volume outcome in cancer care, the Institute of Medicine outlined the need to examine volume-outcome relationships in both surgical and medical interventions.…”
Section: Introductionmentioning
confidence: 99%